Etnomatematika pada Alat Musik Tatong Kedang - Rini, Helena Ratri Puspita; Ramadhani, Nanda Nur; Liko, Veronika Jaga (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Education and culture are two elements that cannot be avoided in everyday life, because culture is a complete and comprehensive unit that applies in society and education is a basic need for every individual in society. Ethnomathematics is seen as a simpler form of mathematics found in formal education. There are mathematical elements found or can be called ethnomathematics in this traditional Tatong musical instrument which can later be used as student teaching materials. This study aims to explore the culture and see more about traditional musical instruments that exist today and can be implemented in mathematics learning. The results of the exploration show that the Tatong musical instrument contains mathematical elements including the spatial structure and the concept of arithmetic sequences from the translation of the beats of the Tatong musical instrument.